ANALISIS STRUKTUR VEGETASI HUTAN MANGROVE DI KAWASAN REKLAMASI PULAU SERANGAN, KOTA DENPASAR - Sundra, I Ketut (Bumi Lestari, 2012)
This research was conducted in Serangan island in August, 2004. Ten plots as sampling units were taken using Systematic Plot Design. Two parameters : Importance Value and Diversity Indices were determined on vegetation analyses. Samples were taken from three different locations. Soil analysis was conducted for determining macro elements content, such as: N, P, K and others organic maters. The result shows that there are 13 species of mangrove found. Five species are classified into ‘pure’ mangrove and others are associate. Rhizophora apiculata (with Important Value, IV, of 103.252 %) and Sonneratia alba (IV 99.663 %) are two species that have high importance value (IV). In addition, the diversity of mangrove in Serangan island is found to be low (diversity indices 0.791). Results of this study indicate that after reclamation, the mangrove ecosystem in Serangan is in unstable conditions.
Keywords: mangrove, reclamation, diversity